Água negra (black water) and overwhelming details: For more-than-nexus approaches to global water–energy–food challenges - Horton, John (2024)
This paper advances multidisciplinary research, policy, education and activisms which cohere around the concept of the ‘water–energy–food (W–E–F) nexus’ via an evidence-led critique of normative forms of nexus-thinking which draws upon research with 3705 diverse young people's (aged 10–24 years) W–E–F experiences in SE Brazil. We consider how the neat, cool, ostensibly authoritative buzzword style of W–E–F nexus-thinking is radically unsettled – and sometimes conceptually-critically overwhelmed – via encounters with social scientific data in practice. In particular, the paper presents two interlinked analyses of data relating to young people's everyday engagements with water resources. First, we present a quantitative analysis of young people's everyday participation with/in water resources, highlighting diversities and inequities in relation to age, gender, ethnicity and social class, among other modes of social–cultural heterogeneity and intersectionality. Second, we present a qualitative narration of young people's water-related anxieties, evidencing their intimate everyday interrelations with watery materialities and insecurities – ‘black water’, ‘muddy water’, ‘shit water’ and all. In so doing, we advance an argument for what we term more-than-nexus-thinking: i.e., forms of research, theory and practice which value the apparent conceptual-ethical clarity and interoperability of nexus-thinking, whilst actively thinking-with complexities and deeply-affecting lived experiences of W–E–F in everyday spaces.